Variation of antioxidants and secondary metabolites in nitrogen-deficient barley plants - Kováčik, Jozef; Klejdus, Bořivoj; Babula, Petr; Jarošová, Markéta (Journal of plant physiology, 2014)
Barley (Hordeum vulgare cv. Bojos) plants cultured in low nitrogen (N) containing Hoagland solution (20 mg/l) were exposed to N deficiency (-N) over 15 days. Plants revealed relatively high tolerance to total N deficit because shoot length was not altered and dry biomass was depleted by ca. 30% while root length increased by ca. 50% and dry biomass remained unaffected. Soluble proteins and free amino acids decreased more pronouncedly in the roots. Antioxidants (glutathione and ascorbic acid) decreased in the shoots but increased or were not affected in the roots. Ascorbate peroxidase and glutathione reductase activities were depleted in shoots and/or roots while guaiacol peroxidase activity was stimulated in the shoots. In accordance, fluorescence signal of reactive oxygen species (ROS) and nitric oxide was elevated in shoots but no extensive changes were observed in roots if +N and -N treatments are compared. At the level of phenolic metabolites, slight increase in soluble phenols and some phenolic acids and strong elevation of flavonoid homoorientin was found in the shoots but not in the roots. Fluorescence microscopy in terms of detection of phenols is also discussed. We also briefly discussed accuracy of quantification of some parameters owing to discrepancies in the literature. It is concluded that N deficiency induces increase in shoot phenolics but also elevates symptoms of oxidative stress while increase in root antioxidants probably contributes to ROS homeostasis aimed to maintain root development.
Keywords: antioxidancia; dusík; ječmen (rod); Reactive Oxygen Species; Oxidative Stress; oxidační stres; Phenolic metabolism; Reactive oxygen species; Fluorescence microscopy; Mineral nutrition; Antioxidants; Hordeum; Oxidative stress; Nitrogen; reaktivní formy kyslíku